2016
DOI: 10.1002/lt.24616
|View full text |Cite|
|
Sign up to set email alerts
|

Late graft hepatitis and fibrosis in pediatric liver allograft recipients: Current concepts and future developments

Abstract: Liver transplantation (LT) in children now has a 20-year survival of >80%, but the longterm outcome of these grafts remains uncertain. Serial protocol liver biopsies after transplantation from several pediatric centres have demonstrated the gradual development of unexplained graft inflammation ("idiopathic" posttransplant hepatitis; IPTH) and graft fibrosis in biopsies obtained >12 months post-LT in children with good graft function and (near) normal liver biochemistry. Although the clinical significance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 71 publications
7
98
1
Order By: Relevance
“…Unfortunately, DSAs were not studied in our patients. Further studies are required to clarify the role of DSAs and other predictive factors of allograft fibrosis …”
Section: Discussionsupporting
confidence: 59%
“…Unfortunately, DSAs were not studied in our patients. Further studies are required to clarify the role of DSAs and other predictive factors of allograft fibrosis …”
Section: Discussionsupporting
confidence: 59%
“…The adverse impact of human leukocyte antigen (HLA) donor‐specific antibodies (DSAs) in liver transplantation (LT) recipients is already established . Many studies have demonstrated associations between de novo donor‐specific antibody (dn‐DSA) with liver allograft injury .…”
mentioning
confidence: 99%
“…Considerable attention has been placed on structural integrity of liver allografts (especially pediatric) because of expectation of decades of morbidity‐free survival . Most studies in pediatric recipients, where primary disease recurrence is not a significant issue, show a high (>40%) incidence of histopathologically significant inflammation and progressive fibrosis by 5‐10 years after transplantation .…”
Section: Importance Of Perspectivementioning
confidence: 99%
“…Considerable attention has been placed on structural integrity of liver allografts (especially pediatric) because of expectation of decades of morbidity‐free survival . Most studies in pediatric recipients, where primary disease recurrence is not a significant issue, show a high (>40%) incidence of histopathologically significant inflammation and progressive fibrosis by 5‐10 years after transplantation . Substantial evidence associates allograft inflammation and fibrosis with smoldering allo‐immunological injury (combined T cell–mediated rejection [TCMR] and chronic antibody‐mediated rejection [cAMR]) as underlying causes .…”
Section: Importance Of Perspectivementioning
confidence: 99%
See 1 more Smart Citation